- #1
b2386
- 35
- 0
Hi all,
Here is my question:
In the [tex]E>U_0[/tex] potential barrier, there should be no reflected wave when the incident wave is at one of the transmisson resonances. Assuming that a beam of particles is incident at the first transmission resonance, [tex]E=U_0+(\frac{\pi^2 h^2}{2mL^2})[/tex], combine the continuity conditions to show that B=0. Here are the continuity conditions:
1st [tex]A+B=C+D[/tex]
2nd [tex]k(A- B)=k^{'}(C-D)[/tex]
3rd [tex]Ce^{ik^{'}L}+De^{-ik^{'}L}=Fe^{ikL}[/tex]
4th [tex]k^{'}(Ce^{ik^{'}L}-De^{-ik^{'}L})=kFe^{ikL}[/tex]
A couple more equations that we already know are [tex]k=\sqrt{\frac{2mE}{h^2}}[/tex] and [tex]k^'=\sqrt{\frac{2m(E-U_0)}{h^2}[/tex]
Here is my attempted solution:
I divided the 4th equation by K and then set equation 3 and 4 equal to each other. I then used the new equation to solve for C in terms of D giving me
[tex]C=De^{-2i \pi}\frac{k^{'}+k}{k^{'}-K}[/tex] where I substituted [tex]\frac{\pi}{L}[/tex] in for k'.
I substituted this result into the first equation to now give me
[tex]A+B={De^{-2i \pi}\frac{k^{'}+k}{k^{'}-K} + D[/tex].
Solving for D gives me
[tex]\frac{A+B}{e^{-2i \pi}\frac{k^{'}+k}{k^{'}-K} + 1} = D[/tex]
Now, plugging in our solutions for D and C into the 2nd equation
[tex]\frac{(A+B)e^{-2i \pi}\frac{k^{'}+k}{k^{'}-K}}{e^{-2i \pi}\frac{k^{'}+k}{k^{'}-K}+1}-\frac{A+B}{e^{-2i \pi}\frac{k^{'}+k}{k^{'}-K}+1}=\frac{k}{k^{'}}(A-B})[/tex]
At this point, it seems impossible to simplify the equation to a point where it is obvious that B = 0. Am I on the right track or is there an easier way?
Here is my question:
In the [tex]E>U_0[/tex] potential barrier, there should be no reflected wave when the incident wave is at one of the transmisson resonances. Assuming that a beam of particles is incident at the first transmission resonance, [tex]E=U_0+(\frac{\pi^2 h^2}{2mL^2})[/tex], combine the continuity conditions to show that B=0. Here are the continuity conditions:
1st [tex]A+B=C+D[/tex]
2nd [tex]k(A- B)=k^{'}(C-D)[/tex]
3rd [tex]Ce^{ik^{'}L}+De^{-ik^{'}L}=Fe^{ikL}[/tex]
4th [tex]k^{'}(Ce^{ik^{'}L}-De^{-ik^{'}L})=kFe^{ikL}[/tex]
A couple more equations that we already know are [tex]k=\sqrt{\frac{2mE}{h^2}}[/tex] and [tex]k^'=\sqrt{\frac{2m(E-U_0)}{h^2}[/tex]
Here is my attempted solution:
I divided the 4th equation by K and then set equation 3 and 4 equal to each other. I then used the new equation to solve for C in terms of D giving me
[tex]C=De^{-2i \pi}\frac{k^{'}+k}{k^{'}-K}[/tex] where I substituted [tex]\frac{\pi}{L}[/tex] in for k'.
I substituted this result into the first equation to now give me
[tex]A+B={De^{-2i \pi}\frac{k^{'}+k}{k^{'}-K} + D[/tex].
Solving for D gives me
[tex]\frac{A+B}{e^{-2i \pi}\frac{k^{'}+k}{k^{'}-K} + 1} = D[/tex]
Now, plugging in our solutions for D and C into the 2nd equation
[tex]\frac{(A+B)e^{-2i \pi}\frac{k^{'}+k}{k^{'}-K}}{e^{-2i \pi}\frac{k^{'}+k}{k^{'}-K}+1}-\frac{A+B}{e^{-2i \pi}\frac{k^{'}+k}{k^{'}-K}+1}=\frac{k}{k^{'}}(A-B})[/tex]
At this point, it seems impossible to simplify the equation to a point where it is obvious that B = 0. Am I on the right track or is there an easier way?